Porosity Estimation in A Natural CO2-Water Reservoir Using Integrated Density-Resistivity Log Approach - Dominicus Sinurat, Pahala; Sasongko, Hari; Samawi, Nabil (Scientific Contributions Oil and Gas, 2025)
Natural CO₂ reservoirs represent important analogues for Carbon Capture and Storage (CCS) and Carbon Capture, Utilization, and Storage (CCUS), as they provide direct evidence of long-term CO₂ retention and trapping mechanisms. This study assesses porosity in a natural carbonate CO₂ reservoir using an integrated density–resistivity log approach. Conventional porosity logs, such as density, neutron, and sonic, often overestimate porosity in carbonate systems due to their limited sensitivity to pore connectivity. To overcome this limitation, density log-derived total porosity was integrated with resistivity-derived effective porosity, allowing for the differentiation between connected and isolated pore systems. Fluid density estimations, including supercritical CO₂ and brine, were computed and validated against standard references to ensure accuracy. The results show that density-only porosity overestimates values by up to 10% in dolomitic intervals, whereas the integrated method provides estimates that are more consistent with core measurements. Isolated porosity, averaging 2% in the upper dolomite and 1.5% in the lower dolomite, was identified as a non-contributing pore volume for injectivity, although it remains relevant for storage capacity. These findings underscore the importance of integrated log interpretation for precise reservoir characterization and offer new insights into evaluating natural CO₂ reservoirs for long-term geological storage.